High-efficiency oxygen production molecular sieve, continuous production process thereof and use thereof

CN121269745BActive Publication Date: 2026-10-30JIANGSU TIANNUO NEW MATERIAL TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511423543.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-30
Publication Date
2026-10-30
Estimated Expiration
2045-09-30

AI Technical Summary

Technical Problem

[0006]本发明要解决的问题是现有技术中锂交换效率低、多次交换破坏低硅铝比分子筛的骨架结构,以及现有生产工艺复杂,不利于大规模工业化生产

Benefits of technology

[0039]3、本发明提供的连续化生产工艺具有以下优点:通过低温、中温、高温三段式恒温晶化,低温利于高活性晶核的形成,中温利于晶体的生长,高温则加速晶化,极大幅度地缩短整个晶化周期,节降能耗,并得到结构稳定且高晶度的制氧分子筛。投用立式压滤机,采用高压挤压与气流脱水技术,实现快速分离晶化浆料,高效去除钠钾离子杂质,自动化程度高。锂交换使用两次逐级带式真空过滤机进行动态、连续、重复锂交换,具有交换效率高、时间短和过程稳定的优点。因此,该连续化生产工艺提升了自动化程度、工艺流程简单、成本低、效率高,易于大规模连续化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121269745B_ABST
    Figure CN121269745B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of oxygen production molecular sieve, and discloses a high-efficiency oxygen production molecular sieve, a continuous production process thereof and an application thereof. Main steps of the continuous production process include: raw material dissolution, constant-temperature crystallization, pressure filtration separation, first-stage lithium exchange, second-stage lithium exchange, flash drying, mixing and rolling, drying and calcination, and screening and packaging. The continuous production process has the following advantages: through three-stage constant-temperature crystallization at low temperature, medium temperature and high temperature, the low temperature is beneficial to the formation of high-activity crystal nucleus, the medium temperature is beneficial to the growth of the crystal, and the high temperature accelerates the crystallization, thereby greatly shortening the entire crystallization period, saving energy consumption, and obtaining oxygen production molecular sieve with stable structure and high crystallinity. The prepared high-efficiency oxygen production molecular sieve has strong mechanical properties, high nitrogen-oxygen separation and good cycle stability, and is applied to the separation of nitrogen and oxygen in the air separation industry, and has the performance advantages of high nitrogen adsorption capacity, high strength and high oxygen production capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-efficiency oxygen-generating molecular sieve, its continuous production process and applications, and belongs to the field of oxygen-generating molecular sieve technology. Background Technology

[0002] In recent years, with the increasing demand for high-purity nitrogen, oxygen, argon, and other gases from various industries, the air separation industry has also developed rapidly. Air separation is an emerging industry based on atmospheric separation technology. With the country's increasing emphasis on energy and the environment, the air separation industry has experienced rapid development and has broad market prospects. Oxygen-generating molecular sieves, as a new type of nitrogen-oxygen separation material, are widely studied due to their high selectivity and recyclability. Commonly used oxygen-generating molecular sieves are lithium-exchanged 5A, 13X, and LSX molecular sieves. In particular, the low silica-to-alumina ratio X-type molecular sieve (Li-LSX) after lithium exchange has a low silica-to-alumina ratio, well-developed pores, good adsorption performance, and excellent nitrogen-oxygen separation effect, making it widely applicable in water adsorption, CO2 adsorption, and gas separation.

[0003] Patent US5268023 indicates that the adsorption capacity only increases rapidly when the lithium exchange rate is greater than 70%. Patent US4859217 states that when the Li+ exchange rate is 99%, the adsorption capacity of nitrogen at normal pressure can reach 1.03 mmol / g, equivalent to 23.07 ml / g. Patents US6806219 and US5174979, among others, achieve higher exchange rates through multiple exchanges or by increasing the amount of Li+ used. Therefore, increasing the Li+ exchange rate... + The degree of exchange becomes the key to preparing high-efficiency oxygen-generating molecular sieves.

[0004] Patent CN101289196A relates to a method for preparing LiLSX molecular sieves, specifically involving passing LSX through a K-type reactor. + KLSX is obtained through multiple exchanges (preferably 5 times), and then processed with NH4. + After multiple exchanges (preferably 5 times), NH4LSX is obtained, and finally processed by Li + The method is to switch to LiLSX via K. + and NH4 + The transitional exchange method, although it improves the utilization rate of Li+, causes some damage to the framework structure of low silica-alumina ratio molecular sieves by repeated exchanges, and the process is repetitive and cumbersome, which is not conducive to large-scale industrial production.

[0005] Patent CN101766987A relates to a lithium-modified low-silicon-aluminum X-type molecular sieve adsorbent and its preparation method. Specifically, the molecular sieve powder is modified by one-stage cross-linking and calcination, two-stage cross-linking and calcination, and three-stage cross-linking to obtain Li-LSX molecular sieve powder, which is then mixed with binders and molding agents to obtain the product. This invention proposes a modification method that alternates between cross-linking and calcination. Although this improves the stability of the LSX molecular sieve framework, this complex modification process is difficult to implement in large-scale industrial production. Summary of the Invention

[0006] The problems to be solved by the present invention are low lithium exchange efficiency, repeated exchange damage to the framework structure of low silicon-to-aluminum ratio molecular sieves, and complex existing production processes, which are not conducive to large-scale industrial production.

[0007] Compared with existing technologies, to achieve this objective, this invention provides a high-efficiency oxygen-generating molecular sieve, its continuous production process, and its applications. The high-efficiency oxygen-generating molecular sieve, prepared through optimized techniques, possesses strong mechanical properties, high nitrogen-oxygen separation efficiency, and good cycle stability. Applied to the separation of nitrogen and oxygen in the air separation industry, it exhibits advantages such as high nitrogen adsorption capacity, high strength, and high oxygen production. This optimized process is simple, low-cost, highly efficient, and easily suitable for large-scale continuous production.

[0008] This invention provides a continuous production process for high-efficiency oxygen-generating molecular sieves, comprising the following steps:

[0009] S1. Raw material dissolution: Solid raw materials and liquid raw materials are separated and automatically and precisely fed into the dissolution vessel for mixing and dissolution. The mixture is mechanically stirred for 2-3 hours to form a homogeneous reaction solution.

[0010] The reaction raw materials consist of a silicon source, an aluminum source, a sodium source, a potassium source, and pure water. The molar ratio of each reaction raw material is: SiO2:Al2O3:Na2O:K2O:H2O=(1.9~2.1):1:(3.5~4.5):(1.8~2.4):(90~120), wherein the silicon source is calculated as SiO2, the aluminum source as Al2O3, the sodium source as Na2O, the potassium source as K2O, and the pure water as H2O.

[0011] The silicon source is either water glass or silica sol; the aluminum source is either sodium aluminate, aluminum hydroxide, or aluminum oxide; the sodium source is a mixed sodium source consisting of sodium hydroxide and sodium bicarbonate in a molar ratio; and the potassium source is a mixed potassium source consisting of potassium hydroxide and potassium bicarbonate in a molar ratio.

[0012] S2. Constant temperature crystallization: The reaction solution is sequentially transferred into a low-temperature crystallization kettle, a medium-temperature crystallization kettle, and a high-temperature crystallization kettle to carry out three-stage constant temperature crystallization at low temperature, medium temperature, and high temperature to obtain a crystallized slurry;

[0013] S3. Filtration separation: Transfer the crystallized slurry to a buffer tank, add cold pure water and stir, cool to 70-90℃, feed into a vertical filter press, discharge the filtrate, and wash the filter cake with pure water until neutral;

[0014] The vertical filter press uses high-pressure extrusion and airflow dehydration technology to achieve rapid separation of crystallized slurry, efficient removal of sodium and potassium ion impurities, and a high degree of automation.

[0015] S4. Primary lithium exchange: The washed filter cake is transferred to the primary belt filter pulping tank, pure water is added, and pulping is carried out for 1-2 hours to obtain the primary exchange material, which is then fed into the primary belt vacuum filter for primary lithium ion exchange.

[0016] The feed rate of the primary exchange material is 1.0–1.5 m³. 3 The feed rate of the primary lithium exchange solution is 1.3–1.8 m³ / h. 3 / h;

[0017] S5. Secondary lithium exchange: The filter cake after primary lithium ion exchange is transferred to the secondary belt filter pulping tank, pure water is added, and the mixture is stirred and pulped for 1-2 hours to obtain secondary exchange material, which is then fed into the secondary belt vacuum filter for secondary lithium ion exchange.

[0018] The feed rate of the secondary exchange material is 1.0–1.5 m³. 3 / h; the feed rate of the secondary lithium exchange solution is 0.8–1.3 m³ / h. 3 / h;

[0019] S6. Flash drying: The filter cake after two-stage lithium-ion exchange is transferred to a flash dryer and flashed at a heating temperature of 220-240℃ to obtain lithium molecular sieve raw powder.

[0020] S7. Mixing and Ball Rolling: Lithium molecular sieve raw powder, binder, auxiliary agent and pure water are mixed in proportion and added to the mixer. After being mixed evenly, the mixture is transferred to the ball rolling machine for ball rolling and sieved to obtain lithium molecular sieve balls with a diameter of 0.5 to 2.0 mm.

[0021] The mass ratio of the lithium molecular sieve raw powder, binder, auxiliary agent and pure water is 1:(0.003~0.009):(0.002~0.006):(0.11~0.15);

[0022] S8. Drying and calcining: The lithium molecular sieve balls after the above screening are first dried in a mesh belt furnace at a temperature of 120-130℃ for 10-12 hours, and then calcined in a vacuum furnace at a temperature of 450-550℃ for 4-6 hours.

[0023] S9. Sieving and Packaging: The calcined lithium molecular sieve balls are transferred to a sieving machine for sieving in two layers. After cooling to 60-70℃, they are packaged and sealed to obtain a high-efficiency oxygen-generating molecular sieve.

[0024] Further, the molar ratio of the mixed sodium source in step S1 is sodium hydroxide:sodium bicarbonate = 1:(1.14~1.38), and the molar ratio of the mixed potassium source is potassium hydroxide:potassium bicarbonate = 1:(0.75~1.05).

[0025] As a further preferred embodiment, the mixed sodium source is sodium hydroxide:sodium bicarbonate with a molar ratio of 1:1.26, and the mixed potassium source is potassium hydroxide:potassium bicarbonate with a molar ratio of 1:0.9. This not only promotes rapid crystal growth in a strongly alkaline environment but also buffers and protects highly active crystal nuclei, further facilitating lithium-ion exchange and improving the lithium uptake rate and ion exchange degree.

[0026] Further, in step S2, the low-temperature crystallization is a constant temperature reaction at 50-70℃ for 4-6 hours, the medium-temperature crystallization is a constant temperature reaction at 100-120℃ for 5-10 hours, and the high-temperature crystallization is a constant temperature reaction at 150-170℃ for 2-6 hours.

[0027] Furthermore, during lithium exchange in steps S4 and S5, the primary and secondary lithium exchange solutions are mixed solutions of lithium sulfate and lithium hydroxide in any proportion, and the pH is adjusted to 10-11 with lithium hydroxide. The lithium exchange temperature is 75-90°C, and the lithium exchange time is 1.5-3.5 hours.

[0028] Furthermore, during lithium exchange in steps S4 and S5, the vacuum degree of the primary and secondary belt vacuum filters is ≤-0.06MPa; the lithium mass concentration in the primary lithium exchange solution is 1.2-2.5%; and the lithium mass concentration in the secondary lithium exchange solution is 0.8-1.5%.

[0029] Furthermore, the binder in step S7 is high-viscosity starch, and the facilitator is hexadecyltrimethylammonium bromide.

[0030] Furthermore, in step S8, the dew point of the atmosphere inside the vacuum furnace is ≤-70℃, and the air intake volume is 200~220m³. 3 / h.

[0031] Furthermore, the screening machine described in step S9 is divided into one-stage and two-stage screening, with the upper screening mesh being 12-16 mesh and the lower screening mesh being 25-35 mesh.

[0032] Practice has proven that the high-efficiency oxygen-generating molecular sieve prepared by the above method can be used to adsorb nitrogen from the air, thereby producing oxygen. It possesses advantages such as high nitrogen adsorption capacity, high strength, and high oxygen production. This optimized process is simple, low-cost, highly efficient, and easily scalable for large-scale continuous production.

[0033] To achieve the above method, the present invention also provides the following production apparatus: a continuous production apparatus for high-efficiency oxygen-generating molecular sieves, comprising a solid feed silo, a liquid feeder, a dissolving kettle, a crystallization reaction system, a buffer tank, a vertical filter press, a belt filter exchange system, a flash dryer, a mixer, a ball mill, a mesh belt furnace, a calcining furnace, and a screening machine; the solid feed silo and the liquid feeder are located above the dissolving kettle; the crystallization reaction system consists of a low-temperature crystallization kettle, a medium-temperature crystallization kettle, and a high-temperature crystallization kettle; the belt filter exchange system consists of a primary belt filter pulping tank, a primary belt vacuum filter, a secondary belt filter pulping tank, and a secondary belt vacuum filter; the dissolving kettle is connected to the crystallization reaction system via pipelines, and The dissolved raw materials are sequentially transferred from the dissolving kettle to a low-temperature crystallization kettle, a medium-temperature crystallization kettle, and a high-temperature crystallization kettle via pumps. The high-temperature crystallization kettle is connected to a buffer tank, and the buffer pipe is connected to a vertical filter press. The vertical filter press is connected to a primary belt filter pulping tank. The belt filter exchange system consists of a primary belt filter pulping tank connected to a primary belt vacuum filter, a secondary belt filter pulping tank connected to a secondary belt vacuum filter, and a primary belt vacuum filter connected to a secondary belt filter pulping tank. The belt filter exchange system is connected to a flash dryer. The flash dryer is connected to a mixer, the mixer is connected to a ball rolling machine, the ball rolling machine is connected to a mesh belt furnace, the mesh belt furnace is connected to a calcining furnace, and the calcining furnace is connected to a screening machine.

[0034] To facilitate more convenient and accurate feeding, the feeding hopper is used to hold solid raw materials, and the bottom of the feeding hopper is equipped with an electronic weighing scale and a discharge port; a liquid feeder is provided above the dissolving kettle, and a mass flow meter is installed above the feed port.

[0035] As a further improvement of the present invention, the bottom of the feeding hopper and the liquid feeder are provided with a protective gas purging bypass for purging residual materials; the protective purging gas is nitrogen, the nitrogen purging time is 5 to 10 minutes, and the nitrogen purging pressure is 0.1 to 0.3 MPa.

[0036] Compared with the prior art, the technical effects of the present invention are reflected in:

[0037] 1. The synthesis of oxygen-generating molecular sieves typically uses a mixed strong base system composed of sodium hydroxide and potassium hydroxide. To avoid excessive alkalinity in the reaction system affecting highly active crystal nuclei, damaging the crystal structure, causing impurity peaks, and reducing crystal purity, the inventors introduced weakly basic salts of the same metal type (NaHCO3, KHCO3) to form carbonate ions (CO32-). 2- HCO3 - The buffer system, through conjugate acid-base pairs, can maintain the stability of the system's pH, which can both promote the rapid growth of crystals in a strong alkaline environment and provide buffer protection for highly active crystal nuclei.

[0038] 2. To improve the lithium exchange rate and degree, this invention uses lithium sulfate, which has strong electrolytic properties and is more easily ionized, in the preparation of the lithium exchange solution. Adding an appropriate amount of lithium hydroxide to adjust the pH value of the target metal ion salt solution significantly improves the lithium ion exchange degree. Furthermore, the traditional batch reactor exchange process is technically optimized by using a two-stage belt vacuum filter for dynamic, continuous, and repeatable lithium exchange, achieving a lithium exchange degree of over 98%. The exchanged lithium solution can be recycled and reused, reducing environmental pollution and production costs. The obtained oxygen-generating molecular sieve exhibits advantages such as high nitrogen adsorption capacity, high strength, and high oxygen production.

[0039] 3. The continuous production process provided by this invention has the following advantages: Through three-stage isothermal crystallization (low temperature, medium temperature, and high temperature), low temperature promotes the formation of highly active crystal nuclei, medium temperature promotes crystal growth, and high temperature accelerates crystallization, significantly shortening the entire crystallization cycle, reducing energy consumption, and yielding oxygen-producing molecular sieves with stable structure and high crystallinity. The use of a vertical filter press, employing high-pressure extrusion and airflow dehydration technology, achieves rapid separation of the crystallized slurry, efficiently removing sodium and potassium ion impurities, and exhibits a high degree of automation. Lithium exchange utilizes two staged belt vacuum filters for dynamic, continuous, and repetitive lithium exchange, offering advantages such as high exchange efficiency, short time, and process stability. Therefore, this continuous production process improves automation, simplifies the process flow, reduces cost, increases efficiency, and is easily applicable to large-scale continuous production. Attached Figure Description

[0040] Figure 1 This invention provides a continuous production process flow diagram for a high-efficiency oxygen-generating molecular sieve. Detailed Implementation

[0041] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0042] Example 1

[0043] like Figure 1The diagram shows a continuous production process flow chart for a high-efficiency oxygen-generating molecular sieve, including a solid feed silo, a liquid feeder, a dissolving kettle, a crystallization reaction system, a buffer tank, a vertical filter press, a belt filter exchange system, a flash dryer, a mixer, a ball mill, a mesh belt furnace, a calcining furnace, and a screening machine. The solid feed silo and liquid feeder are located above the dissolving kettle. The crystallization reaction system consists of a low-temperature crystallization kettle, a medium-temperature crystallization kettle, and a high-temperature crystallization kettle. The belt filter exchange system consists of a primary belt filter pulping tank, a primary belt vacuum filter, a secondary belt filter pulping tank, and a secondary belt vacuum filter. The dissolving kettle is connected to the crystallization reaction system via pipelines, and the dissolved raw material is fed from... The dissolving kettle is sequentially pumped into a low-temperature crystallization kettle, a medium-temperature crystallization kettle, and a high-temperature crystallization kettle; the high-temperature crystallization kettle is connected to a buffer tank, and the buffer pipe is connected to a vertical filter press; the vertical filter press is connected to a primary belt filter pulping tank; the belt filter exchange system consists of a primary belt filter pulping tank connected to a primary belt vacuum filter, a secondary belt filter pulping tank connected to a secondary belt vacuum filter, and a primary belt vacuum filter connected to a secondary belt filter pulping tank; the belt filter exchange system is connected to a flash dryer; the flash dryer is connected to a mixer, the mixer is connected to a ball rolling machine, the ball rolling machine is connected to a mesh belt furnace, the mesh belt furnace is connected to a calcining furnace, and the calcining furnace is connected to a screening machine. The feeding hopper is used to hold solid raw materials, and an electronic weighing scale and a discharge port are provided at the bottom of the feeding hopper; a liquid feeder is provided above the dissolving kettle, and a mass flow meter is installed above the feed port; a protective gas purging bypass is provided at the bottom of the feeding hopper and the liquid feeder for purging residual materials; the protective purging gas is nitrogen, the nitrogen purging time is 5-10 minutes, and the nitrogen purging pressure is 0.1-0.3 MPa;

[0044] The above continuous production process can prepare high-efficiency oxygen-generating molecular sieves according to the following steps:

[0045] S1. Raw material dissolution: Solid raw materials and liquid raw materials are separated and automatically and precisely fed into the dissolution vessel for mixing and dissolution. The mixture is mechanically stirred for 2-3 hours to form a homogeneous reaction solution.

[0046] The reaction raw materials consist of a silicon source, an aluminum source, a sodium source, a potassium source, and pure water. The molar ratio of each reaction raw material is: SiO2:Al2O3:Na2O:K2O:H2O=(1.9~2.1):1:(3.5~4.5):(1.8~2.4):(90~120), wherein the silicon source is calculated as SiO2, the aluminum source as Al2O3, the sodium source as Na2O, the potassium source as K2O, and the pure water as H2O.

[0047] The silicon source is either water glass or silica sol; the aluminum source is either sodium aluminate, aluminum hydroxide, or aluminum oxide; the sodium source is a mixed sodium source consisting of sodium hydroxide and sodium bicarbonate in a molar ratio; and the potassium source is a mixed potassium source consisting of potassium hydroxide and potassium bicarbonate in a molar ratio.

[0048] Wherein, the molar ratio of the mixed sodium source is sodium hydroxide:sodium bicarbonate = 1:(1.14~1.38), and the molar ratio of the mixed potassium source is potassium hydroxide:potassium bicarbonate = 1:(0.75~1.05). Preferably, the mixed sodium source is sodium hydroxide:sodium bicarbonate with a molar ratio of 1:1.26, and the mixed potassium source is potassium hydroxide:potassium bicarbonate with a molar ratio of 1:0.9.

[0049] S2. Constant Temperature Crystallization: The reaction solution is sequentially transferred to a low-temperature crystallization kettle, a medium-temperature crystallization kettle, and a high-temperature crystallization kettle for three-stage constant temperature crystallization: low-temperature crystallization is carried out at a constant temperature of 50-70℃ for 4-6 hours, medium-temperature crystallization is carried out at a constant temperature of 100-120℃ for 5-10 hours, and high-temperature crystallization is carried out at a constant temperature of 150-170℃ for 2-6 hours to obtain crystallized slurry;

[0050] S3. Filtration separation: Transfer the crystallized slurry to a buffer tank, add cold pure water and stir, cool to 70-90℃, feed into a vertical filter press, discharge the filtrate, and wash the filter cake with pure water until neutral;

[0051] The vertical filter press uses high-pressure extrusion and airflow dehydration technology to achieve rapid separation of crystallized slurry, efficient removal of sodium and potassium ion impurities, and a high degree of automation.

[0052] S4. Primary lithium exchange: The washed filter cake is transferred to the primary belt filter pulping tank, pure water is added, and pulping is carried out for 1-2 hours to obtain the primary exchange material, which is then fed into the primary belt vacuum filter for primary lithium ion exchange.

[0053] The feed rate of the primary exchange material is 1.0–1.5 m³. 3 The feed rate of the primary lithium exchange solution is 1.3–1.8 m³ / h. 3 / h;

[0054] S5. Secondary lithium exchange: The filter cake after the first lithium ion exchange is transferred to the pulping tank of the secondary belt filter, pure water is added, and the mixture is stirred and pulped for 1-2 hours to obtain the secondary exchange material, which is then fed into the secondary belt vacuum filter for secondary lithium ion exchange.

[0055] The feed rate of the secondary exchange material is 1.0–1.5 m³. 3 / h; the feed rate of the secondary lithium exchange solution is 0.8–1.3 m³ / h. 3 / h;

[0056] The vacuum degree of the primary and secondary belt vacuum filters is ≤-0.06MPa. The lithium mass concentration in the primary lithium exchange solution is 1.2-2.5%; the lithium mass concentration in the secondary lithium exchange solution is 0.8-1.5%; the primary and secondary lithium exchange solutions are mixed solutions of lithium sulfate and lithium hydroxide in any proportion, and the pH is adjusted to 10-11 with lithium hydroxide. The lithium exchange temperature is 75-90℃; and the lithium exchange time is 1.5-3.5h.

[0057] S6. Flash drying: The filter cake after secondary lithium exchange is transferred to a flash dryer and flashed at a heating temperature of 220-240℃ to obtain lithium molecular sieve raw powder.

[0058] S7. Mixing and Ball Rolling: Lithium molecular sieve raw powder, binder, auxiliary agent and pure water are mixed in proportion and added to the mixer. After being mixed evenly, the mixture is transferred to the ball rolling machine for ball rolling and sieved to obtain lithium molecular sieve balls with a diameter of 0.5 to 2.0 mm.

[0059] The mass ratio of lithium molecular sieve raw powder, binder, auxiliary agent and pure water is 1:(0.003~0.009):(0.002~0.006):(0.11~0.15), the binder is high viscosity starch and the auxiliary agent is hexadecyltrimethylammonium bromide.

[0060] S8. Drying and Calcination: The lithium molecular sieve balls after sieving are first dried in a mesh belt furnace at 120-130℃ for 10-12 hours, and then calcined in a vacuum furnace at 450-550℃ for 4-6 hours. The dew point of the atmosphere in the vacuum furnace is ≤-70℃, and the air intake volume is 200-220 m³ / h. 3 / h.

[0061] S9. Sieving and Packaging: The calcined lithium molecular sieve balls are transferred to a sieving machine for two-layer sieving. The upper layer has a mesh size of 12-16 mesh, and the lower layer has a mesh size of 25-35 mesh. After sieving, the mixture is cooled to 60-70℃, packaged, and sealed to obtain a high-efficiency oxygen-generating molecular sieve.

[0062] In Example 1, the silicon-to-aluminum ratio in the reaction raw materials is one of the key factors for realizing the present invention. Based on Example 1, the molar amount of Al2O3 in the aluminum source is kept constant, while the molar amount of SiO2 in the silicon source is changed. The effects of different molar amounts of aluminum and silicon sources on the relative crystallinity are shown in Table 1 below.

[0063] Table 1. Effect of different molar amounts of aluminum and silicon sources on relative crystallinity.

[0064]

[0065]

[0066] Table 1 shows that the silicon source can be either water glass or silica sol, and the aluminum source can be either sodium aluminate, aluminum hydroxide, or aluminum oxide, with little difference in their technical effects. When the molar amount of Al2O3 in the aluminum source remains constant, and the molar amount of SiO2 in the silicon source is either low or high, the relative crystallinity of the prepared molecular sieve is below 95%. Low relative crystallinity leads to unstable molecular sieve structure, weak strength, and decreased oxygen-generating activity. Therefore, the preferred molar ratio is SiO2:Al2O3 = (1.9–2.1):1.

[0067] In the sodium-potassium system for synthesizing oxygen-generating molecular sieves, the different ratios of sodium and potassium sources play a crucial role in the synthesis process, directly affecting the charge balance in the synthesis system and acting as a structure guide. Based on Example 1, the results of changing the ratios of sodium and potassium sources are shown in Table 2 below.

[0068] Table 2. Effect of different molar amounts of sodium and potassium sources on relative crystallinity.

[0069]

[0070]

[0071] Table 2 shows that experiments 1-9 represent crystallization results with only the amount of sodium source varied, experiments 10-14 represent crystallization results with only the amount of potassium source varied, and experiments 5, 12, and 15 represent crystallization results with only the amount of pure water varied. This indicates that changes in water dosage have little effect on the relative crystallinity, but the amount of water is sufficient to dissolve the solid raw materials and disperse them uniformly. Therefore, the preferred molar ratio is Na₂O:K₂O:H₂O = (3.5-4.5):(1.8-2.4):(90-120), with a relative crystallinity ≥95%.

[0072] Furthermore, the synthesis of oxygen-generating molecular sieves utilizes a mixed strong base system composed of sodium hydroxide and potassium hydroxide. To prevent excessive alkalinity in the reaction system from damaging the highly active crystal nuclei, causing impurity crystal peaks, and reducing crystal purity, the results of varying the molar ratios of the mixed sodium and potassium sources, based on Example 1, are shown in Tables 3 and 4 below.

[0073] Table 3. Effect of molar amounts of different mixed sodium sources on relative crystallinity

[0074]

[0075] Table 4. Effect of molar amounts of different mixed potassium sources on relative crystallinity

[0076]

[0077] The tables show that, by analyzing the relative crystallinity obtained from experiments 1-5 in Table 3 and comparative experiments 3-A and 3-B, and from experiments 1-5 in Table 4 and comparative experiments 3-a and 3-b, the following conclusions can be drawn: the molar ratio of the mixed sodium source is sodium hydroxide:sodium bicarbonate = 1:(1.14-1.38), preferably 1:1.26; the molar ratio of the mixed potassium source is potassium hydroxide:potassium bicarbonate = 1:(0.75-1.05), preferably 1:0.9, and the relative crystallinity of both is ≥95%. Therefore, the mixed sodium and potassium sources are formed by introducing weakly basic salts of the same metal type (NaHCO3, KHCO3) to form carbonate ions (CO32-). 2- HCO3 - The buffer system, with its conjugate acid-base pairs, can maintain the stability of the system's pH, promoting rapid crystal growth in a strongly alkaline environment while also providing buffer protection for highly active crystal nuclei.

[0078] This invention optimizes the traditional intermittent reactor lithium exchange process by using a two-stage belt vacuum filter for dynamic, continuous, and repetitive lithium exchange. Based on Example 1, the lithium exchange process parameters were adjusted, and the results are shown in Table 5 below.

[0079] Table 5. Effect of changing lithium exchange process parameters on lithium exchange degree.

[0080]

[0081]

[0082] Table 5 shows that experiments 1-5 represent the results of primary lithium exchange; experiments 6-10 represent the results of secondary lithium exchange; and comparative experiments 3-B and 8-b represent the results of traditional batch reactor lithium exchange processes. The traditional batch reactor process exhibits a significantly lower degree of lithium exchange, resulting in incomplete exchange and substantial waste of lithium resources. By employing a dynamic, continuous, and repetitive lithium exchange process using two stages of belt vacuum filtration, the primary lithium exchange rate reached 86-94%, and the secondary process significantly improved the exchange rate to over 98%, demonstrating a technical advantage over the traditional batch reactor process. Furthermore, comparative analysis of experiments 3-A and 3-C, and 8-a and 8-c, indicates that adding an appropriate amount of lithium hydroxide to adjust the pH of the target metal ion salt solution during lithium ion exchange significantly enhances the degree of lithium ion exchange. Therefore, the optimized lithium exchange process offers advantages such as high exchange efficiency, short processing time, and process stability.

[0083] In practical applications, lithium molecular sieve powder is unstable and easily affected by moisture and dispersion, severely impacting nitrogen and oxygen separation efficiency. Therefore, mixing and balling the lithium molecular sieve powder can improve its mechanical stability and flowability, facilitating transportation and use. Lithium molecular sieve powder, binder, auxiliaries, and pure water are mixed in a specific ratio and added to a mixer until homogeneous. The mixture is then transferred to a balling machine for balling. Based on Example 1, the adsorption performance and compressive strength were tested by screening the mixing mass ratio. Adsorption performance was assessed using the static adsorption method, placing the material in a constant temperature and humidity chamber and calculating the adsorption amount by detecting changes in oxygen concentration. Compressive strength was tested using a universal testing machine, measuring the compressive strength of the material by applying pressure. The test results are shown in Table 6 below.

[0084] Table 6. Effects of different mixing mass ratios on adsorption performance and compressive strength

[0085]

[0086] Table 6 shows that: Experiments 1 and 2 represent test data obtained by adding only a binder or an auxiliary agent; the results indicate that adding only a single substance does not achieve the same effect as the technical effect of this invention. Experiments 3-11 represent test data obtained by changing the amount of binder added; Experiments 12-16 represent test data obtained by changing the amount of auxiliary agent added; Experiments 7 and 14 represent test data obtained by changing the amount of pure water added, indicating that changes in the amount of pure water added have little impact on the test results, but the amount of pure water should be sufficient to dissolve the solid raw materials and form a homogeneous mixed solution. Comparing the above test data, the results indicate that the preferred mixing mass ratio is 1:(0.003-0.009):(0.002-0.006):(0.11-0.15), with high-viscosity starch as the binder and hexadecyltrimethylammonium bromide as the auxiliary agent. High-viscosity starch has a hydrophilic skeleton composed of numerous hydroxyl groups, and the molecular structure of hexadecyltrimethylammonium bromide consists of hydrophilic quaternary ammonium groups and hydrophobic long-chain alkyl groups. When the two are combined, the hydrophobic portion of hexadecyltrimethylammonium bromide is embedded into the skeleton chain of high-viscosity starch through physical adsorption or chemical bonding, changing its surface properties and giving it hydrophobicity. Then, it is bonded, mixed and rolled with lithium molecular sieve powder to further improve the water absorption properties of the oxygen-generating molecular sieve itself, ultimately achieving the effect of hydrophobic, stable and efficient oxygen production.

[0087] As is well known, molecular sieves are a core component of oxygen concentrators, and their performance directly affects the oxygen production efficiency and lifespan of the machine. Accelerated aging testing is an experimental method used to evaluate the aging performance of molecular sieve materials in an oxygen environment. By artificially enhancing conditions such as oxygen concentration, temperature, and humidity, it simulates the oxygen environment that molecular sieve materials might encounter in actual use, thereby accelerating their aging process. This method can quickly assess the performance changes of materials in an oxygen environment and predict their lifespan.

[0088] We examined the factors affecting the practical application of oxygen-generating molecular sieves: adsorption performance, compressive strength, and wear rate. Adsorption performance is a crucial performance indicator of molecular sieves, directly impacting the oxygen production efficiency of oxygen generators. Compressive strength and wear rate are durability indicators of molecular sieves, directly affecting the service life of oxygen generators. Adsorption performance was assessed using a static adsorption method, placing the material in a constant temperature and humidity chamber and calculating the adsorption capacity by monitoring changes in oxygen concentration. Compressive strength was tested using a universal testing machine, measuring the material's compressive strength by applying pressure. Wear rate was assessed through abrasion tests, simulating the frictional environment of actual use and measuring changes in mass. The simulated test results are shown in Table 7 below.

[0089] Table 7. Simulation Test Results of Oxygen Generating Molecular Sieves Operating Time

[0090]

[0091] Table 7 shows that the obtained oxygen-generating molecular sieve, after long-term simulated performance testing, still maintains a high nitrogen adsorption value ≥32ml / g, compressive strength ≥13N, and a very low abrasion rate ≤0.25%. Therefore, the high-efficiency oxygen-generating molecular sieve prepared by the above technical means has strong mechanical properties, high nitrogen-oxygen separation efficiency, and good cycle stability. When applied to the separation of nitrogen and oxygen in the air separation industry, it has the performance advantages of high nitrogen adsorption capacity, high strength, and high oxygen production.

[0092] Furthermore, the continuous production process provided by this invention employs a three-stage isothermal crystallization process: low temperature, medium temperature, and high temperature. Low temperature promotes the formation of highly active crystal nuclei, medium temperature facilitates crystal growth, and high temperature accelerates crystallization. This significantly shortens the entire crystallization cycle, reduces energy consumption, and yields oxygen-producing molecular sieves with stable structures and high crystallinity. A vertical filter press, utilizing high-pressure extrusion and airflow dehydration technology, rapidly separates the crystallized slurry, efficiently removing sodium and potassium ion impurities with a high degree of automation. Lithium exchange utilizes two staged belt vacuum filters for dynamic, continuous, and repetitive lithium exchange, offering advantages such as high exchange efficiency, short time, and process stability.

[0093] In summary, the high-efficiency oxygen-generating molecular sieve prepared using the above techniques possesses strong mechanical properties, high nitrogen-oxygen separation efficiency, and good cycle stability. When applied to the separation of nitrogen and oxygen in the air separation industry, it exhibits advantages such as high nitrogen adsorption capacity, high strength, and high oxygen production. The continuous production process provided by this invention improves automation, simplifies the process flow, reduces costs, increases efficiency, and facilitates large-scale continuous production.

[0094] This invention is not limited to the above embodiments. Based on the technical solutions disclosed in this invention, those skilled in the art can make some substitutions and modifications to some of the technical features without creative effort, and all such substitutions and modifications are within the protection scope of this invention.

Claims

1. A continuous production process for high-efficiency oxygen-generating molecular sieves, characterized in that... Includes the following steps: S1. Raw material dissolution: Solid raw materials and liquid raw materials are separated and automatically and precisely fed into the dissolution vessel for mixing and dissolution. The mixture is mechanically stirred for 2-3 hours to form a homogeneous reaction solution. The raw materials consist of silicon source, aluminum source, sodium source, potassium source and pure water, and the molar ratio of the raw materials is: SiO2:Al2O3:Na2O:K2O:H2O=(1.9~2.1):1:(3.5~4.5):(1.8~2.4):(90~120), wherein the silicon source is calculated as SiO2, the aluminum source as Al2O3, the sodium source as Na2O, the potassium source as K2O and the pure water as H2O; The silicon source is either water glass or silica sol; the aluminum source is either sodium aluminate, aluminum hydroxide, or aluminum oxide; the sodium source is a mixed sodium source composed of sodium hydroxide and sodium bicarbonate, wherein the molar ratio of sodium hydroxide to sodium bicarbonate in the mixed sodium source is 1:(1.14~1.38); the potassium source is a mixed potassium source composed of potassium hydroxide and potassium bicarbonate, wherein the molar ratio of potassium hydroxide to potassium bicarbonate in the mixed potassium source is 1:(0.75~1.05). S2. Isothermal Crystallization: The reaction solution is sequentially transferred to a low-temperature crystallization kettle, a medium-temperature crystallization kettle, and a high-temperature crystallization kettle for three-stage isothermal crystallization to obtain a crystallized slurry; wherein, the low-temperature crystallization is a constant temperature reaction at 50~70℃ for 4~6 hours, the medium-temperature crystallization is a constant temperature reaction at 100~120℃ for 5~10 hours, and the high-temperature crystallization is a constant temperature reaction at 150~170℃ for 2~6 hours; S3. Filtration separation: Transfer the crystallized slurry to a buffer tank, add cold pure water and stir, cool to 70~90℃, feed into a vertical filter press, discharge the filtrate, and wash the filter cake with pure water until neutral; S4. Primary Lithium Exchange: The washed filter cake is transferred to the primary belt filter pulping tank, pure water is added, and pulping is carried out for 1-2 hours to obtain the primary exchange material. This material is then fed into the primary belt vacuum filter for primary lithium-ion exchange; the feed flow rate of the primary exchange material is 1.0-1.5 m³ / h. 3 The feed flow rate of the primary lithium exchange solution is 1.3~1.8 m³ / h. 3 / h; S5. Secondary Lithium Exchange: The filter cake after primary lithium-ion exchange is transferred to the secondary belt filter pulping tank, pure water is added, and the mixture is stirred and pulped for 1-2 hours to obtain secondary exchange material. This secondary exchange material is then fed into the secondary belt vacuum filter for secondary lithium-ion exchange; the feed rate of the secondary exchange material is 1.0-1.5 m³. 3 The feed rate of the secondary lithium exchange solution is 0.8~1.3 m³ / h. 3 / h; In steps S4 and S5, during lithium exchange, both the primary and secondary lithium exchange solutions are mixed solutions of lithium sulfate and lithium hydroxide, with the pH adjusted to 10-11 using lithium hydroxide. The lithium exchange temperature is 75-90°C, and the lithium exchange time is 1.5-3.5 hours. The vacuum degree of the primary and secondary belt vacuum filters is ≤-0.06 MPa. The lithium mass concentration in the primary lithium exchange solution is 1.2-2.5%, and the lithium mass concentration in the secondary lithium exchange solution is 0.8-1.5%. S6. Flash drying: The filter cake after secondary lithium exchange is transferred to a flash dryer and flashed at a heating temperature of 220~240℃ to obtain lithium molecular sieve raw powder; S7. Mixing and Ball Rolling: Lithium molecular sieve raw powder, binder, auxiliary agent, and pure water are mixed in a proportion and added to a mixer. After mixing evenly, the mixture is transferred to a ball rolling machine for ball rolling and sieving to obtain lithium molecular sieve balls with a diameter of 0.5~2.0mm. The mass ratio of the lithium molecular sieve raw powder, binder, auxiliary agent, and pure water is 1:(0.003~0.009):(0.002~0.006):(0.11~0.15). The binder is high-viscosity starch, and the auxiliary agent is hexadecyltrimethylammonium bromide. S8. Drying and calcination: The lithium molecular sieve balls after sieving are first dried in a mesh belt furnace at a temperature of 120~130℃ for 10~12h, and then calcined in a vacuum furnace at a temperature of 450~550℃ for 4~6h; the dew point of the atmosphere in the vacuum furnace is ≤-70℃, and the air intake volume is 200~220m³. 3 / h; S9. Sieving and Packaging: The calcined lithium molecular sieve balls are transferred to a sieving machine for two-layer sieving. The upper layer is 12-16 mesh and the lower layer is 25-35 mesh. After sieving, the mixture is cooled to 60-70℃, packaged, and sealed to obtain a high-efficiency oxygen-generating molecular sieve.

2. The continuous production process of a high-efficiency oxygen-generating molecular sieve according to claim 1, characterized in that: The molar ratio of sodium hydroxide to sodium bicarbonate in the mixed sodium source is 1:1.26, and the molar ratio of potassium hydroxide to potassium bicarbonate in the mixed potassium source is 1:0.

9.

3. The continuous production process of a high-efficiency oxygen-generating molecular sieve according to claim 1, characterized in that: The vertical filter press described in step S3 uses high-pressure extrusion and airflow dehydration technology; the lithium liquid after primary lithium-ion exchange and secondary lithium-ion exchange in steps S4 and S5 is recycled and reused.

4. A high-efficiency oxygen-generating molecular sieve, characterized in that: Prepared using the continuous production process according to any one of claims 1-3.

5. The use of the high-efficiency oxygen-generating molecular sieve according to claim 4, characterized in that: The molecular sieve is used to adsorb nitrogen from the air, thereby producing oxygen.

Citation Information

Patent Citations

  • Method for preparing LiLSX molecular screen

    CN101289196A

  • Lithium-containing modified low silicon-aluminum X type molecular sieve adsorbent and preparation method thereof

    CN101766987A

  • Process for separating nitrogen from mixtures thereof with less polar substances

    US4859217A

  • Mixed ion-exchanged zeolites and processes for the use thereof in gas separations

    US5174979A

  • Nitrogen adsorption with highly Li exchanged X-zeolites with low Si / Al ratio

    US5268023A